Multidisciplinary treatment and long-term outcomes in six patients with leiomyosarcoma of the inferior vena cava - Jihoon T Kim; Teawon Kwon; Yongpil Cho; Sung Shin; Sunggyu Lee; Deokbog Moon (Annals of surgical treatment and research, 2012)
Purpose: Leiomyosarcoma (LMS) of the inferior vena cava (IVC) is a rare primary soft tissue sarcoma. Few reports have detailed the tumor features, treatment strategies, and long-term outcomes in IVC LMS patients. The present report describes the treatment and long-term outcomes of six patients with IVC LMS. Methods: We reviewed six consecutive cases of IVC LMS treated at the University of Ulsan College of Medicine, Asan Medical Center from August 1998 to June 2010. Results: The patients comprised five females and one male, and had a median age of 44 years (range, 25 to 64 years). All tumors were suprarenal. The tumors were located between the hepatic and renal veins (i.e., middle segment; n = 5 [83%]), or above the hepatic veins (i.e., upper segment; n = 1 [17%]). Prosthetic IVC replacement using polytetrafluoroethylene grafts was performed in five patients, and the remaining patient underwent only tumor resection and IVC ligation. There were no intraoperative or postoperative deaths. The mean tumor size was 9.3 cm (range, 5 to 20 cm), and five of the six tumors were high grade. The mean follow-up period was 80 months (range, 6 to 118 months). The median survival period was 94 months. Recurrence occurred in all patients. Distant recurrence resulted in three patients undergoing lung resection and three patients undergoing thigh muscle resection. Conclusion: IVC LMS is a rare but serious disease. Although surgical resection combined with chemoradiotherapy was not completely curative, it resulted in long-term patient survival, even in patients with advanced tumors. KCI Citation Count: 16